Emotions and interests in social representations about the environmental problem of arsenic in water in Tandil (Buenos Aires, Argentina) - Lampert, Damian Alberto (2023)
Qualitative research is presented, recovering the discourse of the students. We worked with a survey and an interview in a 7th year course of the Chemistry Technical at a secondary school in Tandil with a population of 20 people. The first, as a qualitative technique, used those points from the ROSES questionnaire and some items, associated with the theme of arsenic in water, were added in order to incorporate the components of the representations where emotions can be found. On the other hand, the qualitative interview, evoked from images, used a set associated with the theme (water filters, cartographic maps, images of the disease, among others). This created a better communication with the students as well as other aspects. The students had to classify an image in relation to the following items: sadness, fear, distrust, helplessness, anger, worry and indifference. The selection of those emotions was based on previous studies conducted on social representations of environmental issues, such as climate change. The results obtained showed that the students have a great interest in environmental issues and recognize their active role in relation to solving these aspects. In addition, it was obtained that more than 80% of the students expressed their interest in learning more about the subject. Likewise, in relation to the images, the students expressed the following emotions: sadness, helplessness, worry and fear. Faced with these results, the different emotions are taken into account at stake for the subsequent development of a contextualized didactic sequence in the city of Tandil, with the aim of working on the problem of arsenic in water and the emotions obtained from the interview.